Performance Analysis of Solar Power Generation System with A Dual Input Buck Boost DC-AC Inverter and Boost Power Converter (International Journal of Scientific Research in Science and Technology, 2025)
This paper presents a hybrid generation system that includes power-smoothing features using a Fuzzy Logic Controller (FLC). The proposed system integrates solar, wind, and grid power sources along with a control topology based on FLC. The FLC is used to control power flow and maintain system stability by adjusting the energy dispatch strategy according to real-time conditions. Its effectiveness in enhancing system stability, minimizing power fluctuations, and optimizing energy usage is demonstrated through simulations and analysis. Comparative studies between FLC and other control techniques highlight the advantages of using fuzzy logic for power smoothing in hybrid generation systems. The findings emphasize FLC's robustness and flexibility as a control solution for improving the performance and reliability of hybrid energy systems, thereby supporting the integration of renewable energy into power grids.
Keywords: Solar PV Array; inverter; Microgrid; Battery; fuzzy logic Controller